2018
DOI: 10.1002/jhet.3381
|View full text |Cite
|
Sign up to set email alerts
|

Microwave‐assisted Synthesis, Characterization, and Density Functional Theory Study of Biologically Active Ferrocenyl Bis‐pyrazoline and Bis‐pyrimidine as Organometallic Macromolecules

Abstract: Organometallic macromolecules such as ferrocenyl bis‐pyrazoline (2, 3) and bis‐pyrimidine (4, 5) derivatives were synthesized by reacting ferrocenyl bis‐chalcone 1 with thiosemicarbazide/phenylhydrazine/guanidine hydrochloride/thiourea, respectively, under microwave irradiation. Ferrocenyl bis‐chalcone 1 was synthesized by reacting acetyl ferrocene with terephthalaldehyde. Synthesized compounds were characterized by using IR, 1H NMR, 13C NMR, EI‐MS, and elemental analysis. In vitro antibacterial activity again… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…14 Several studies have reported the synthesis of bis-pyrazolines and bis-pyrimidines from bis-chalcones using microwave heating and ultrasound irradiation. [15][16][17] We here report the design and synthesis of three new bis-heterocyclic compounds from a bis-chalcone that was prepared by the reaction between acetophenone and terephthalaldehyde using the Claisen-Schmidt method. The title compounds were tested and their antimicrobial activities on three bacteria and two types of fungi were studied.…”
Section: Introductionmentioning
confidence: 99%
“…14 Several studies have reported the synthesis of bis-pyrazolines and bis-pyrimidines from bis-chalcones using microwave heating and ultrasound irradiation. [15][16][17] We here report the design and synthesis of three new bis-heterocyclic compounds from a bis-chalcone that was prepared by the reaction between acetophenone and terephthalaldehyde using the Claisen-Schmidt method. The title compounds were tested and their antimicrobial activities on three bacteria and two types of fungi were studied.…”
Section: Introductionmentioning
confidence: 99%
“… 11 Additionally, molecules that contain more than one pyrimidine core have been reported to act as antibacterial and antifungal agents. 12 , 13 …”
Section: Introductionmentioning
confidence: 99%
“…Pyrimidines have been used as suitable starting materials for the synthesis of novel scaffolds that are parent to DNA bases and derivatives, thus targeting compounds with relevant biological and pharmacological properties. For example, trihalomethyl-substituted pyrimidines have been used as caspase inhibitors, hepatitis C inhibitors, , antiplasmodials, NTPDase inhibitors, as well as anticancer agents . Additionally, molecules that contain more than one pyrimidine core have been reported to act as antibacterial and antifungal agents. , …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, microwave assisted reactions has arisen as one of the most convenient and reproducible methods for synthesis of various heterocyclic compounds due to its green and sustainable nature. In view of this, a number of authors have reported the microwave-assisted synthesis of various organic compounds, which have been widely applied in the drug discovery field, due to enhanced reaction rates, high yields, improved purity, and greener reaction condition [2,3,4,5,6].…”
Section: Introductionmentioning
confidence: 99%